14-year trends and resistance patterns of blood and cerebrospinal fluid cultures in children under three years old. Issue 5 (November 2021) - Takata, Junko; Kelly, Dominic F; Sadarangani, Manish; Jeffery, Katie; Drysdale, Simon B
Highlights: Number of cultures taken increased over time, but proportion positive declined. Most blood cultures were taken from children under 2 days old but few were positive. Cases of vaccine-preventable organisms were few and declined over time. Resistance to empirical agents exist but resistance to a second agent were low. Summary: Objectives: Bacterial infections are a major cause of UK paediatric hospitalisations, yet longitudinal data on causative organisms or antimicrobial resistance are scarce. This retrospective analysis describes trends in blood and cerebrospinal fluid (CSF) cultures and resistance patterns in children under three years old from a large UK centre. Methods: All culture results, and resistance data for Gram-negative rods (GNR) in blood cultures, collected between January 2005 and December 2018 were extracted from Oxford University Hospitals NHS Foundation Trust microbiology database. Results: Of 49, 298 samples, 6.7% of blood and 3.1% of CSF cultures were positive for bacterial growth; 2.3% and 1.1%, respectively grew pathogens. Number of cultures taken increased over time; the proportion growing pathogens declined. Resistance of GNR to first-line antimicrobials was 9.3% to gentamicin (neonatal units), and 17.1% and 25.8% to ceftriaxone (paediatric ED and wards respectively). Resistance to any two of ceftriaxone, ciprofloxacin, gentamicin, or meropenem was ≤ 6% in both areas. Conclusions: The proportion of positive cultures declined over time. Resistance of GNR to empirical antimicrobials were observed, but resistance to a second agent were lower. Our study informs clinician decisions on when, and to which antimicrobials, to escalate if a child is not improving on empirical therapy.